A sustainable yarn tension control technique for optimizing textile dyeing efficiency and water use - Rana Ahmed; Motaz Amer; Lina Ismail (PLoS ONE, 2026)
The textile dyeing sector contributes significantly to excessive water and energy use and environmental pollution. Managing yarn tension during the rewinding process is a crucial challenge in textile dyeing, as it has a direct impact on yarn quality, resource consumption, and overall efficiency. Traditional tension control techniques ignore how tension variation affects the production of wastewater and the need for chemical treatment. Using a digital signal processor (TMS320F28335), this study introduces a novel event-driven yarn tension control method for soft winding machines that maintains ideal, constant tension across fine, medium, and thick cotton yarn counts. The suggested method dramatically reduces tension variance, as demonstrated by experimental validation conducted at a leading Egyptian cotton yarn producer. This decreases yarn defects by 35% and allows for a 27% increase in machine speed without sacrificing yarn quality. Most significantly, liquor ratio data show that optimized tension management reduces water consumption during dyeing by 65–70%, thereby lowering chemical use and wastewater generation. Additionally, energy use dropped by almost 20%, improving process sustainability. This integrated strategy promotes the triple bottom line of social, economic, and environmental advantages and is consistent with cleaner manufacturing principles. The results provide a scalable methodology for environmentally friendly textile production, especially appropriate for developing nations with limited resources.